A case of isolated IgG4-related lung disease in a teenager - E. V. Sokol; V. I. Vasilyev; N. V. Kokosadze (Современная ревматология)
IgG4-related disease (IgG4-RD) is a rare immune-mediated fibroinflammatory disease that is characterized by the occurrence of nodules in one or more organs and proceeds in most patients with the elevated levels of IgG4 in serum and/or in the tissues of the affected organs. The majority of patients are elderly men, and the disease in most cases has a slowly progressing systemic course. The cases of isolated IgG4-related injury to the viscera, which are much less common than the systemic type of the disease, are a very difficult differential diagnosis, and biopsy of these organs is associated with technical difficulties and poses a threat to the patient's health. The paper describes just such a case. It is interesting from several points of view: firstly, a rare site (solitary pulmonary nodular lesion); secondly, clinical and laboratory features (childhood onset, no immunological abnormalities – both higher serum IgG4 levels and lower complement components).Clinicians should remember that IgG4-RD does not always have a systemic course and characteristic serological markers. In these cases, histological verification of the diagnosis is of particular importance. If the histological pattern of a fibroinflammatory pseudotumor is identified, especially in the presence of multiple nodules, IgG4-RD should always be included in the differential diagnosis.